STC3141 improves acute lung injury through neutralizing circulating histone in rat with experimentally-induced acute respiratory distress syndrome - Ge, Yangyang; Wang, Chenchen; Yao, Chenye; Wang, Yong; Zheng, Yuduo; Luo, Junjie; Chen, Jiayi; Wang, Yu; Wang, Fuquan; Wang, Li; Lin, Yun; Shi, Lin; et al. (Frontiers in Pharmacology, 2023)
Background: Acute respiratory distress syndrome (ARDS) remains a challenge because of its high morbidity and mortality. Circulation histones levels in ARDS patients were correlated to disease severity and mortality. This study examined the impact of histone neutralization in a rat model of acute lung injury (ALI) induced by a lipopolysaccharide (LPS) double-hit. Methods: Sixty-eight male Sprague-Dawley rats were randomized to sham (N=8, received saline only) or LPS (N=60). The LPS double-hit consisted of a 0.8 mg/kg intraperitoneal injection followed after 16 hours by 5 mg/kg intra-tracheal nebulized LPS. The LPS group was then randomized into five groups: LPS only; LPS + 5, 25, or 100 mg/kg intravenous STC3141 every 8 hours (LPS+L, LPS+M, LPS+H, respectively); or LPS + intraperitoneal dexamethasone 2.5 mg/kg every 24 hours for 56 hours (LPS+D) The animals were observed for 72 hours. Results: LPS animals developed ALI as suggested by lower oxygenation, lung edema formation, and histological changes compared to the sham animals. Compared to the LPS group, LPS+H and +D groups had significantly lower circulating histone levels and lung wet-to-dry ratio, and the LPS+D group also had lower BALF histone concentrations; the blood neutrophils and platelets counts in LPS+D group did not change, meanwhile, the LPS+L, +M and +H groups had significantly lower neutrophil counts and higher platelet counts in the blood; the total number of BALF WBC, platelet counts, MPO and H3 were significantly lower in the LPS+L, +M, +H and +D groups than in the LPS only group; and the degree of inflammation was significantly less in the LPS+L, +M, +H and +D groups, moreover, inflammation in the LPS+L, +M and +H animals showed a dose-dependent response; finally, the LPS+L, +M, +H and +D groups had improved oxygenation compared to the LPS group, and there were no statistical differences in PCO2 or pH among groups. All animals survived. Conclusion: Neutralization of histone using STC3141, especially at high dose, had similar therapeutic effects to dexamethasone in this LPS double-hit rat ALI model, with significantly decreased circulating histone concentration, improved acute lung injury and oxygenation.